Pengaruh Self-esteem terhadap Celebrity Worship pada Mahasiswa Penggemar Boyband NCT - Ayu Chodijahtul Kubro; Siti Qodariah (UNISBA Press, 2024)
Abstract. The development of Korean culture in Indonesia was triggered by the contributions made by boy groups and girl groups that managed to steal the attention of the public. One example of a boy band that is currently popular is NCT. These idols influence their fans, inspiring a sense of love in fans, which in turn increases self-confidence and a positive view of oneself. This phenomenon contributes to a stronger bond between fans and their idols, even creating a parasocial relationship known as